The project leadership work of value creation: Reflections from Follett - Dicle Kortantamer (Project Leadership and Society)
Project scholars are increasingly turning their attention to the role of projects in tackling environmental and societal wicked problems. This essay contributes to attempts to understand the navigation of the dynamic processes of project value construction in the face of these wicked problems by advancing the socialised perspective of leadership. Drawing on Follett, it offers four key enhancements: 1) an emphasis on interweaving diverse and potentially contradictory values, 2) the recognition that values should dynamically evolve in relation to both emerging events and active confrontations of conflicting values that are made possible by flexible forms of contacting, 3) an openness to learning about alternative ways of relating to nature in shaping values, and 4) opening the collective practice of leadership to broad participation.